KEWIRAUSAHAAN BERBASIS PROMISE AND PERIL ERA INDUSTRI 4.0 TERHADAP PRILAKU ENTREPRENEUSHIP REMAJA KARANG TARUNA CAKRAWALA TANJUNG PRIOK - Kuspriyono, Taat (AGUSPATI Research Institute, 2022)
The progress of digitalization has had its own impact on humans, especially in the field of technology. Industry 4.0 has changed the shift from human power to machine power. This is also felt by youth youth groups who take advantage of Entrepreneurship Based on Promise and Peril in the Industrial Era 4.0 in doing business. To find out the relationship that occurs between Promise-Based Entrepreneurship and Peril in the Industrial Age 4.0 Against Youth Entrepreneurship Behavior, a research method used is a quantitative method, by distributing questionnaires to the object of research, in this case youth Karang Taruna Horizon, Tanjung Priok. The research was conducted with the aim of knowing to what extent youth youth groups are accustomed to doing entrepreneurship based on 4.0. The results of this study show that each variable has a very high relationship. The correlation results of promise-based entrepreneurship (X1) on entrepreneurship behavior (Y) are 0.874 entrepreneurial parallels (X2) on entrepreneurship behavior (Y) are 0.934 and two star signs appear. which means showing a high level of correlation.